Stanisława Vincenza filozofia współistnienia w perspektywie powojennych stosunków polsko-żydowskich - Czarnik, Mirosław (Tematy i Konteksty, 2017)
The text considers the possibility of functioning of the philosophy of coexistence supported by Stanisław Vincenz the author of Na wysokiej połoninie (On the high meadow) in the perspective of postwar Polish-Jewish relations. He does that in reference to widely treated historical context (from the 1940s up to the present times) noting that postwar Polish-Jewish relations are of extremely complex character and are realized between selfless friendship, at times even heroism and xenophobia and aggressive antisemitism. The text also mentions the criteria of strangeness/hostility and familiarity functioning between both nations. The conclusion of the text is a well-argumented statement that in the present Polish reality practical realization of Vincenz’s philosophy showing equality and equality of values in mutual interethnic relations is difficult, however, in the future perspective and „long lasting” (understood in accordance with the intention of Ferdinand Braudel) is not impossible and desired indeed.